Formulation and Evaluation of a Drug-in-Adhesive Patch for Transdermal Delivery of Colchicine - Yaran Lei; Guobao Yang; Feng Du; Jiahe Yi; Liangzhu Quan; Hanhan Liu; Xun Zhou; Wei Gong; Jing Han; Yuli Wang; Chunsheng Gao (MDPI AG, 2022)
Gout is one of the most prevalent rheumatic diseases, globally. Colchicine (COL) is the first-line drug used for the treatment of acute gout. However, the oral administration of COL is restricted, owing to serious adverse reactions. Therefore, this study aimed to develop a drug-in-adhesive (DIA) patch to achieve transdermal delivery of COL. We investigated the solubility of COL in different pressure-sensitive adhesives (PSAs) using slide crystallization studies. The COL-DIA patches were optimized based on in vitro skin penetration studies and evaluated by in vivo pharmacokinetics and pharmacodynamics. The results showed that the optimized COL-DIA patch contained 10% COL, Duro-Tak 87-2516 as PSA, 5% oleic acid (OA) and 5% propylene glycol (PG) as permeation enhancer, exhibiting the highest in vitro cumulative penetration amount of COL (235.14 ± 14.47 μg∙cm−2 over 48 h). Pharmacokinetic studies demonstrated that the maximum plasma drug concentration (Cmax) was 2.65 ± 0.26 ng/L and the mean retention time (MRT) was 37.47 ± 7.64 h of the COL-DIA patch, effectively reducing the drug side effects and prolonging drug activity. In addition, pharmacodynamic studies showed the patch significantly decreased the expression levels of inflammatory factors of gouty rats and reduced pathological damage in the ankle joint of rats, making it an attractive alternative to the administration of COL for the treatment of gout.